Dampak Kompetensi Digital terhadap Peningkatan Daya Saing UMKM di Kabupaten Serang - Zahrotul Hayat; Munawaroh Munawaroh (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Digitalization has changed the way MSMEs operate, such as interacting with customers and competing in the market. Business developments in the current digital era mean that every business actor must also change the way they run their business, such as by utilizing digital platforms. This research discusses the importance of digital competence in increasing the competitiveness of MSMEs in the market. This research aims to provide understanding for business actors to improve their competence in using digital technology in running their business. The approach used is a qualitative descriptive method, using a research sample of 50 respondents who are considered to represent the population, namely MSMEs in Serang Regency. The research results show that digital competence has a positive effect and has a big impact on the competitiveness of MSMEs in the market.